معهد سيدي تواتي ببجاية وجهوده في تعليم القرآن الكريم والعلوم الشرعية. Sidi Touati Institute In Bejaia And Its Efforts In Teaching The Holy Quran And Islamic Sciences. - أودني بلال (University of Eloued جامعة الوادي, 2023)
ملخص: عُرفت بجاية قديما بكثرة الزوايا، ومن أبرزها زاوية سيدي تواتي في القرن التاسع، فقد كانت مركز إشعاع علمي إلى أن حوّلها المستدمر الفرنسي إلى ثكنة عسكرية، ولم تنل الزاوية حظّها من العناية بعد الاستقلال؛ حيث طالها الإهمال، إلى أن قيّض الله لها جمعية إحياء معهد سيدي تواتي؛ فبذلت جهودا في تعليم القرآن الكريم والقراءات والعلوم الشرعية، هذا ما بيّنته في هذه الورقة البحثية مستعينا بالمنهج الوصفي مع توظيف آلية التحليل، وقد توصّلت إلى جملة من النتائج أهمها ما يلي: - وُفق المعهد إلى حد بعيد في إحياء مآثر زاوية سيدي تواتي. - خرّج المعهد العديد من حفظة القرآن الكريم. – اهتمّ المعهد بتدريس العلوم الشرعية معتمدا على التدرج. Abstract: Bejaia was known in the past for the proliferation of its zawiyas (religious institute), and one of the most prominent of these zawiyas was Sidi Touati Zawiya in the 9th century. It was a center of scientific radiance until it was transformed into a military barracks by the French invader. After Algeria’s independence, the zawiya did not receive its fair share of attention and suffered neglect. However, by the will of God, an association was created to revive Sidi Touati Institute, where efforts were deployed to teach the Holy Quran, recitation methods, and Islamic sciences. This is what I presented in this research paper, using a descriptive methodology and applying an analytical approach. I have obtained several results, the most important of which are as follows: (i) The institute made great strides in reviving the legacy of Sidi Touatii Zawiya, (ii) the institute produced many Quran memorizers, (iii) the institute relies on a progressive approach in teaching Islamic sciences
Keywords: التواتي; بجاية; التعليم; القرآن; العلوم الشرعية; Bejaia; Education; Quran; Islamic sciences; Sidi Touati